Desain Website Sebagai Media Promosi Marketing Mix Pada UMKM Key Snack Bandung - Rochmawati, Irma; Albar, Deni; Fauzi, Ahmad Nurzaeni (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
Key Snack is an MSME located in Bandung and operates in the culinary sector in the form of cakes. Key Snack already has a P-IRT business license for its products and has a vision to be able to grow rapidly like culinary providers of cakes that are much more established. However, unfortunately, Key Snack MSME products are not yet known to the wider public. For this reason, promotion is one solution to support the marketing of Key Snack MSME products. This research aims to produce an applied object that is useful for industry and to find a formula for promoting Key Snack MSMEs. Producing design products that are expected to have a social or economic impact after the research results are applied, one of which is website design. The method used in this research uses a Pre-Experimental design research approach. In pre-experimental research, variables are not strictly limited, so there is the possibility of outcomes caused by various aspects that influence the respondent. It is hoped that the results of this research will show the correct formulation of the concept in representing Key Snack MSME promotional media in its application.